Upaya Penguatan Pemahaman Guru: Pelatihan Peningkatan Guru Terhadap Penyebab Siswa Sulit Membaca - Ratnawati, Sri; Vera, Amanda Putri; Maharani, Keysha Alea (LPMP Imperium, 2026)
This community service activity aimed to enhance teachers’ competencies in identifying and addressing students’ reading difficulties. The main problems observed among students included weak articulation skills and low phonological awareness, which contributed to inadequate foundational literacy abilities. The training was conducted at Darussalam Elementary School on September 6, 2025, and involved 20 participants consisting of kindergarten, elementary, and junior high school teachers. The training employed lectures, group discussions, and hands-on practice, with a focus on articulation and phonological exercises. The evaluation was carried out using the Kirkpatrick model at the reaction and learning levels through feedback questionnaires, pretests, and posttests. The results indicated a significant improvement between participants’ pretest and posttest scores, demonstrating the effectiveness of the training in strengthening teachers’ understanding of the causes of reading difficulties. Observational data further supported these findings by showing improved accuracy in participants’ pronunciation of letters. Despite these positive outcomes, several technical challenges were encountered, such as large group sizes and suboptimal classroom conditions. Overall, the training proved effective and is recommended for continued implementation with improvements in technical and management aspects.